2016
DOI: 10.1007/s00125-016-4072-7
|View full text |Cite
|
Sign up to set email alerts
|

IRS proteins and diabetic complications

Abstract: IRS proteins are cellular adaptor molecules that mediate many of the key metabolic actions of insulin. When tyrosine is phosphorylated by the activated insulin receptor, IRS proteins recruit downstream effectors, such as phosphoinositide 3-kinase and mitogen-activated protein kinase, in order to elicit cellular responses such as glucose uptake, lipid metabolism and cell proliferation. There are two main IRS proteins in humans (IRS1 and IRS2), both of which are widely expressed. Given their central role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 81 publications
(121 reference statements)
1
69
0
Order By: Relevance
“…Since adult stem cells are present in PBMCs which have similar expression profiles to UBC [39], one could expect similar actions by Metadichol on these cells leading to observed improvements that we have documented in diabetes patients [21][22][23]. The study shows highly related biologically functional gene clusters are the key in targeting diseases.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Since adult stem cells are present in PBMCs which have similar expression profiles to UBC [39], one could expect similar actions by Metadichol on these cells leading to observed improvements that we have documented in diabetes patients [21][22][23]. The study shows highly related biologically functional gene clusters are the key in targeting diseases.…”
Section: Resultsmentioning
confidence: 60%
“…We recently presented clinical case studies that showed the effectiveness of Metadichol in treatment of diabetes and related complications like wound healing [20][21][22]. IRS1 and IRS2 have been shown to play an essential role in the insulin signaling pathway [23]. Increase in IRS2 expression in β-cells has been shown to be essential for growth and function [24].…”
Section: Analysis Of Amplicons By Semi Quantitative Rt Pcrmentioning
confidence: 99%
“…However, the effects of the IRS-1 genotype on prediabetic mediated features were not known. Recently the researchers showed that this gene is not only associated with Type 2 diabetes in different populations but also it may have a significant correlation with diabetic complications, particularly with coronary artery disease (CAD) and obesity (9)(10)(11). Another gene that was investigated in this study was perilipin (PLIN) (rs4578621).…”
Section: Introductionmentioning
confidence: 86%
“…Though IRS1 and IRS2 share similar structural and functional features, 43 they have complementary roles and expression patterns that depend on tissue type and 44 physiological state (Haeusler et al, 2017). These differences are illustrated by divergent 45 phenotypes in knockout mice: whereas IRS1 knockout mice exhibit insulin resistance that 46 is compensated by increased pancreatic β cell mass, IRS2 knockout mice exhibit β cell 47 failure and resultant diabetes (Lavin et al, 2016). Distinct roles for IRS1 and IRS2 can 48 also be observed within the same tissue.…”
Section: Introduction 32mentioning
confidence: 99%